73.8k views
3 votes
Which of the following occurs within the solution process for 3√5x-2-3√4x=0

Which of the following occurs within the solution process for 3√5x-2-3√4x=0-example-1
User Shyamala
by
5.3k points

2 Answers

2 votes

Answer:

C

Explanation:

User Elijah Glover
by
5.3k points
1 vote

For this case we have the following expression:


\sqrt [3] {5x-2} - \sqrt [3] {4x} = 0

If we add to both sides of the equation
\sqrt [3] {4x} we have:


\sqrt [3] {5x-2} = \sqrt [3] {4x}

To eliminate the roots we must raise both sides to the cube:


(\sqrt [3] {5x-2}) ^ 3 = (\sqrt [3] {4x}) ^ 3\\5x-2 = 4x

So, the correct option is the option c

Answer:

Option C

User Mike Kaply
by
5.3k points